2014
DOI: 10.1161/strokeaha.114.005603
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Functional Dependence Despite Successful Revascularization in Large-Vessel Occlusion Strokes

Abstract: Background and Purpose High revascularization rates in large-vessel occlusion strokes treated by mechanical thrombectomy are not always associated with good clinical outcomes. We evaluated predictors of functional dependence despite successful revascularization among patients with acute ischemic stroke treated with thrombectomy. Methods We analyzed the pooled data from the Multi Mechanical Embolus Removal in Cerebral Ischemia (MERCI), Thrombectomy Revascularization of Large Vessel Occlusions in Acute Ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
60
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 24 publications
19
60
1
1
Order By: Relevance
“…In accordance with previous studies, our study also found that old age [27], severe neurological deficits [27], high baseline glucose level [28], pneumonia [29,] and sICH [30] were independent predictors for poor functional outcome. Moreover, small baseline infarct core (ASPECTS 8-10) [31], successful revascularization (mTICI 2b-3) [27,32], good collateral status (2-3) [33,34], and OTT ≤6 h [27,35,36] were protective factors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous studies, our study also found that old age [27], severe neurological deficits [27], high baseline glucose level [28], pneumonia [29,] and sICH [30] were independent predictors for poor functional outcome. Moreover, small baseline infarct core (ASPECTS 8-10) [31], successful revascularization (mTICI 2b-3) [27,32], good collateral status (2-3) [33,34], and OTT ≤6 h [27,35,36] were protective factors.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, small baseline infarct core (ASPECTS 8-10) [31], successful revascularization (mTICI 2b-3) [27,32], good collateral status (2-3) [33,34], and OTT ≤6 h [27,35,36] were protective factors. As shown in our study, sICH was the strongest predictor, which was associated with 14 times increased risk for poor functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, rapid reperfusion may lead to reperfusion injury and hemorrhagic transformation (HT) in acute stroke 4 5. Minor HT is usually inconsequential, but the parenchymal hematoma has been shown to be associated with a poor clinical outcome 3 6 7. Preventing severe HT is the next frontier of stroke intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical course under medical treatment, including intravenous heparin therapy, is extremely severe, with a mortality rate ranging from 40% to 86% (1). The major predictive factor for a good outcome is the speed of occluded vessel recanalization (2,3). According to recent publications, mechanical thrombectomy seems to be a safe and efficient technique for achieving recanalization in cases of acute arterial occlusion (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%